An An Analysis of Code-Switching and Patterns between Students and A Lecturer in Higher Education Speaking Class - Bayyinah, Sahara; Sakina, Rahma; Widianingsih, Ayang Winda Sri; Nugraha, Muhammad Anjar (Ma'soem University, 2024)
By examining the patterns of code-switching and code-mixing among Ma'soem University fourth-semester English education students, this study aims to analyze the pattern of code-switching and code-mixing in speaking classes. The study employs a qualitative descriptive methodology, capturing instances of these linguistic behaviors through observations, interviews, and documentation. The study groups communicative functions, contextual triggers, and different types of language alternation according to the theories of Grosjean (1982), Myers-Scotton (1993), and Muysken (2000). The results show that code-switching and code-mixing improve comprehension, facilitate cross-cultural learning, and greatly improve students' educational experiences. The most common pattern is insertional code-switching, which enables students to use vocabulary from several languages to more accurately communicate complicated ideas, especially when literal translations are inadequate. On the other hand, tag-switching seems to be the least common and frequently happens accidentally. The complex interplay among language proficiency, communicative requirements, and cultural identity in the context of education is reflected in these patterns. The results of this study imply that code-switching and code-mixing are essential to successful communication, cultural expression, and language acquisition rather than just being linguistic phenomena.